Pleurodesis with Thulium Cyber Laser versus talc poudrage: a comparative experimental study. Issue 7 (September 2016) - Droghetti, Andrea; Vannucci, Jacopo; Bufalari, Antonello; Bellezza, Guido; De Monte, Valentina; Marulli, Giuseppe; Bottoli, Maria; Giovanardi, Michele; Daddi, Niccolò; De Angelis, Verena; Moriconi, Franco; Puma, Francesco
Abstract Sclerosing fluids to achieve pleurodesis could be hardly replaced for bed-side procedures, but other devices may be successfully applied during thoracoscopy. Thulium Cyber Laser was experimented for this purpose and compared to talc poudrage. Twenty pigs underwent operative videothoracoscopy (VATS). Ten models were subjected to double-port VATS and parietal pleura photoevaporation using Thulium Cyber Laser™ (TCL) 150 W 2010 nm on the posterior third of three ribs; the pleural surface was homogeneously treated inside the target perimeter. The remaining ten pigs underwent uniportal thoracoscopy; talc poudrage was performed using the current clinical practice dosage (1 g/18 kg) with accurate talc powder spread over the whole pleural surface. All models were followed up for 60 days. Pleurodesis firmness was graded on a three-tier scale (none-moderate-firm) and site-matching topographical expectancy was evaluated. TCL produced pleurodesis in all models: 7/10 were firm and 3/10 moderate. Talc poudrage pleurodesis was firm in 4/10 and moderate in 6/10. Pleural adhesions were found exclusively in the treated area after laser treatment, while talc created a wide spectrum of effects, most commonly anarchic jagged adhesions obliterating less than 50 % of the pleural cavity (7/10), mostly declivous. The pathologist found more aggressive inflammation (sometimes severe) in the talc group. Expected localized pleurodesis was always registered in laser group (10/10), while talc poudrage was found poorly effective if consistent pleurodesis is expected in an apico-dorsal position (2/10). Laser pleurodesis appears more homogeneous, qualitatively not inferior, and topographically more predictable than talc pleurodesis. Parietal photoevaporation seems effective and the localized pleurodesis is reproducible.